Preparation and characterization of ZSM-5 zeolite - ANAS BOUSSAA, Sabiha; NİBOU, Djamel; BENFADEL, Karime; TALBİ, Lamia; BOUKEZZATA, Assia; OUADAH, Yahia; ALLAM, Djaouida (International Journal of Computational and Experimental Science and Engineering, 2023)
Recently, zeolites attracted considerable research attention because they exhibit adsorption properties, ion exchange capabilities and a good catalytic property, a specific pore size distribution; a unique chemical and thermal properties and several applications. Actually zeolites play a crucial role as a catalyst to capture and convert Carbone dioxide into valuable products. In the present work, hydrothermal synthesis of ZSM-5 zeolite crystals, with composition of the chemical products 0.01 Al2O3,1SiO2,2 NaOH, 0.15 TPABr, 18.34 H2O at 170°C for 48 hours (2 days) at Ph 11 is described. Results of characterization of the ZSM-5 zeolite by XRD, FTIR, EDAX, SEM, TGA, are presented and discussed.